Population Growth, Foreign Direct Investment, and Human Development Index on Poverty In Indonesia - Rezki, Amaliah; Baharuddin, Dahlia; Selong, Abbas; Manulusi, Muhammad Ridwan (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
Poverty, as a national issue, cannot be solely resolved by the government through various development policies but also requires collective responsibility from all development stakeholders, including the community itself. The aim of this research is to analyze the influence of population growth, Foreign Direct Investment, and Human Development Index on the poverty rate in Indonesia. Secondary data from the Indonesian Central Bureau of Statistics for the period 2010 to 2022 were utilized for this study. The research population encompasses the entire Indonesian population. Non-Probability Sampling technique with a purposive sampling approach was employed to select a representative sample. Analytical methods included descriptive analysis, multiple linear regression analysis, and hypothesis testing such as t-test, F-test, and coefficient of determination to examine the statistical significance of the observed relationships. The research findings reveal that population growth and Foreign Direct Investment have a positive and significant impact on the poverty rate in Indonesia. However, Foreign Direct Investment shows a negative and significant influence on the poverty rate in Indonesia. Conversely, the Human Development Index does not exhibit a significant impact on the poverty rate. These findings contribute to a better understanding of the factors affecting the poverty rate in Indonesia and can serve as a basis for formulating more effective policies to address poverty-related issues in the future.